Quality of life of Venezuelan migrants in Brazil during the COVID-19 pandemic - Iaralyz Fernandes Farias; Anete Trajman; Paulo Nadanovsky; Manuel Ribeiro; Eduardo Faerstein (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
The economic, social, and health crisis in Venezuela has resulted in the largest forced migration in recent Latin American history. The general scenario in host countries influence migrants' self-perception of quality of life, which can be understood as an indicator of their level of integration. The COVID-19 pandemic has exacerbated socioeconomic and health vulnerabilities, especially for forced migrants. We hypothesized that the adverse circumstances faced by Venezuelan migrants during the pandemic have deepened their vulnerability, which may have influenced their perception of quality of life. This study aims to evaluate the quality of life of Venezuelan migrants in Brazil during the COVID-19 pandemic. We assessed the quality of life of 312 adult Venezuelan migrants living in Brazil using the World Health Organization WHOQOL-BREF quality of life assessment, which was self-administered online from October 20, 2020, to May 10, 2021. The associations of quality of life and its domains with participants' characteristics were analyzed via multiple linear regression models. Mean quality of life score was 44.7 (±21.8) on a scale of 0 to 100. The best recorded mean was in the physical domain (66.2±17.8) and the worst in the environmental domain (51.1±14.6). The worst quality of life was associated with being a woman, not living with a partner, lower household income, and discrimination based on nationality. Factors associated with overall quality of life and respective domains, especially income and discrimination, were also observed in other studies as obstacles to Venezuelan migrants. The unsatisfactory quality of life among Venezuelans living in Brazil may have been worsened by the pandemic during the study period.